Do Leaders Matter? National Leadership and Growth Since World War II* - Jones, Benjamin F.; Olken, Benjamin A. (Quarterly Journal of Economics, 2005)
Economic growth within countries varies sharply across decades.This paper examines one explanation for these sustained shifts in growth-changes in the national leader.We use deaths of leaders while in office as a source of exogenous variation in leadership, and ask whether these plausibly exogenous leadership transitions are associated with shifts in country growth rates.We find robust evidence that leaders matter for growth.The results suggest that the effects of individual leaders are strongest in autocratic settings where there are fewer constraints on a leader's power.Leaders also appear to affect policy outcomes, particularly monetary policy.The results suggest that individual leaders can play crucial roles in shaping the growth of nations."There is no number two, three, or four . . .